Gamification and Student Motivation: Evaluating E-Learning Engagement from an Educational Psychology Perspective - Sappaile, Baso Intang; Jenheri, Jenheri; Sari, Arum Fandan; Nampira, Ardi Azhar (Yayasan Minang Darussalam, 2025)
This study investigates the impact of gamification on student motivation and engagement in e-learning environments from an educational psychology perspective. The research aims to evaluate how game-based elements—such as points, badges, leaderboards, and challenges—affect intrinsic and extrinsic motivation, learning persistence, and cognitive engagement among students. Using a mixed-methods approach, data were collected through surveys, system analytics, and interviews involving 210 undergraduate students enrolled in online learning courses. Quantitative results show that gamified features significantly enhance students’ intrinsic motivation and foster higher participation rates, while qualitative findings reveal that meaningful design and feedback mechanisms contribute to a more positive learning experience. The study highlights that gamification is most effective when aligned with psychological principles such as self-determination, goal orientation, and flow theory. These findings provide important implications for instructional designers and educators in creating engaging digital learning environments that promote sustained motivation and academic achievement.